Coupled FHD-MHD free convection of a hybrid nanoliquid in an inversed T-shaped enclosure occupied by partitioned porous media - Izadi, Mohsen; Öztop, Hakan Fehmi; Sheremet, Mikhail A.; Mehryan, S. A. M.; Abu-Hamdeh, Nidal (Taylor & Francis Inc, 2019)
The article treats the study on free convection of a hybrid nanoliquid confined within contrariwise T-shaped enclosure saturated by two porous media with different material and structure. Nanocomposite particles of multiwall carbon nanotubes-Fe3O4 are dispersed into water. Variable magnetic source located to the bottom wall has been analyzed in terms of heat transport performance and nanofluid motion behavior in the enclosure. The governing equations with boundary conditions formulated using the primitive dimensionless variables have been numerically worked out by the finite element technique. Impacts of the Hartmann number, magnetic number, Rayleigh number, ratio of thermal conductivity, porosity ratio, the Darcy number, and convective heat transfer coefficient at solid-nanofluid interface have been investigated. It has been found that low values of dimensionless convection parameter ratio at the border between solid and nanoliquid phases characterize high values of the nanofluid dimensionless convective heat transfer parameter. The average Nusselt number for the solid state has maximum value for high quantities of ratio of Darcy number and low values of dimensionless convection parameter ratio at the border between solid and nanoliquid phases.
Keywords: Conjugate Natural-Convection; Heat-Transfer; Nanofluid Flow; Mixed-Convection; Cavity; Channel; Wall; Ltne